Latin American Immigrant Women in Spain: Racism and Assimilation Experiences - Hernández Martínez, Camila (2022)
From the fields of gender studies and anthropology, this interdisciplinary study analyzes the racist experiences lived by immigrant Latin American women in Spain, which influence the adherence of the subjects to cultural assimilation techniques. Assimilation is an acculturation strategy where individuals reject the culture of origin in an attempt to fully incorporate themselves into the culture of the host society. Rejecting the Latin American culture through practices and discourses is a way of protecting oneself against the systematic racism experienced in the European territory, as well as a way of getting closer to the white privilege of natives. The methodology used has been qualitative through an intersectional analysis with a gender perspective of semi-structured individual interviews carried out with ten Latin American women immigrants in Spain. In conclusion, on one hand, it is verified that the integration discourses produced by the European institutions have been incorporated by the immigrant subjects, often being interpreted as a duty of assimilation or adaptation that would imply the rejection of the culture of origin. On the other hand, it is also recognized that, simultaneously, women put into action multiple processes of agency and empowerment during their migration journeys.